Artery of Percheron stroke: A review - Aleksey A. Kulesh; Dmitry A. Demin (Consilium Medicum)
Ischemic stroke caused by the obstruction of the artery of Percheron is a rare type of ischemic stroke, in which one arterial branch supplying blood to both thalamuses and the middle brain is occluded, which leads to the depression of consciousness, paresis of vertical vision, and cognitive impairment. Due to the atypical symptoms ("stroke-chameleon"), the diagnosis is often not verified in time, which deprives the patient of the most effective treatment – thrombolytic therapy. The review aims to increase clinicians' awareness of this subtype of stroke.